Pointwise Approximation of Piecewise Convex Function in L_p, Quasi Normed Spaces (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Some authors introduced direct inequalities for the constrained approximation of convex and piecewise convex functions in C[-1,1] with restricted degree of approximation. Here we study the pointwise constrained approximation of piecewise convex functions by pointwise polynomials .